Pengaruh Literasi Keuangan, Gaya Hidup, Dan Gender Terhadap Pengelolaan Keuangan Mahasiswa Akuntansi Universitas Muhammadiyah Sukabumi - Kusmiati Agustin, Mia; Wahyu Nugroho, Gatot; Martaseli, Evi (Universitas Muhammadiyah Metro, 2024)
This study aims to determine the influence of financial literacy, lifestyle and gender on the financial management of accounting students of Muhammadiyah Sukabumi University. This study used quantitative methods with data collection techniques using primary data through questionnaires with a population of 566 accounting study program students of Muhammadiyah Sukabumi University. The sampling technique used the slovin formula and obtained a sample of 85 respondents. The data in this study used SPSS version 23 with multiple linear analysis testing. The results of this study show that financial literacy, lifestyle and gender have a partial and simultaneous effect on the financial management of accounting students of Muhammadiyah Sukabumi University.